Composite structure-based transparent ultra-broadband metamaterial absorber with multi-applications. (27th April 2020) - Liu, Rui; Zhang, Binzhen; Duan, Junping; Dong, Lin; Yu, Juan; Zhang, Zhonghe
Abstract: In this paper, an approach is proposed to realize optically transparent metamaterial absorber (OTMA) with ultra-broadband absorption properties by using composite resonant structure. The indium tin oxide (ITO) resistive film is used to construct the resonant structure to induce high ohmic loss and broaden the bandwidth of the resonances, thus achieves more than 90% absorptivity in the wide bandwidth of 8–30.3 GHz, which can cover the X and Ku bands of the airborne and surveillance radar signal frequencies. The novelty of designed structure lies in the properties of larger absorption bandwidth (covering X, Ku, K and part of Ka bands), lower thickness, and absorption capacity over a wide range of incident angles. Moreover, by replacing the intermediate air spacer with polydimethylsiloxane (PDMS) and polymethyl methacrylate (PMMA) dielectrics, the OTMAs that can be used for conformal applications and rigid window glass of stealth armament are designed. This strategy provides more flexibility for the applications of broadband OTMA in different occasions, and has potential application prospects in radar stealth system, EM shielding and transparent RF equipment fields. The average optical transmittance of the whole structure in the visible light range exceeds 78%.